2012
DOI: 10.1111/j.1461-9563.2012.00596.x
|View full text |Cite
|
Sign up to set email alerts
|

Frost increases beech susceptibility to scolytine ambrosia beetles

Abstract: In the early 2000s, beech forests in Western Europe suffered from a so far unexplained burst of mortality. Necroses, ambrosia‐beetle and fungal attacks were observed on the trunks. The symptoms were similar to previous events reported throughout the 20th Century. One current hypothesis is that these phenomena were related to early frost events for which the trees were physiologically unprepared and which made them vulnerable to biotic attacks. In the present study, we aimed to test this hypothesis further, by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 25 publications
1
43
0
Order By: Relevance
“…the limited studies that have examined the connection between freeze damage and insect susceptibility in trees, one (Thomson, Nicotra, & Steinbauer, 2001) revealed increased growth of two insect species on Eucalyptus, and another showed increased attraction of beetles to Fagus (LaSpina, De Cannière, Dekri, & Grégoire, 2013), suggesting that freeze damage may render trees more susceptible to insect attack. To date, studies examining the effects of freeze damage on trees have not addressed impacts on aboveground-belowground biomass allocation, or the connection between freeze-induced changes in particular plant traits (e.g., phytochemistry) and plant-insect interactions.…”
mentioning
confidence: 99%
“…the limited studies that have examined the connection between freeze damage and insect susceptibility in trees, one (Thomson, Nicotra, & Steinbauer, 2001) revealed increased growth of two insect species on Eucalyptus, and another showed increased attraction of beetles to Fagus (LaSpina, De Cannière, Dekri, & Grégoire, 2013), suggesting that freeze damage may render trees more susceptible to insect attack. To date, studies examining the effects of freeze damage on trees have not addressed impacts on aboveground-belowground biomass allocation, or the connection between freeze-induced changes in particular plant traits (e.g., phytochemistry) and plant-insect interactions.…”
mentioning
confidence: 99%
“…; La Spina et al. ). This causes the crowns to compensate for the lack of water by starting to die back, senescing at an accelerated rate and breaking down and exporting increased amounts of nutrients via the phloem either to storage in the roots or reallocation to new growth or reproductive tissues (Gates ; Bryant et al.…”
Section: Discussionmentioning
confidence: 98%
“…As a drought begins and intensifies, the shallow surface soils dry out, killing the trees' feeding roots (Thomas et al 2002;Anderegg et al 2013;La Spina et al 2013). This causes the crowns to compensate for the lack of water by starting to die back, senescing at an accelerated rate and breaking down and exporting increased amounts of nutrients via the phloem either to storage in the roots or reallocation to new growth or reproductive tissues (Gates 1964;Bryant et al 1983;Masclaux et al 2000;Soudry et al 2005;Millard and Grelet 2010;White 2011;Gonda-King et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The current study was conducted with experimental conditions which may not simulate those in the field. For example, La Spina et al (2013) found increased preference, but not performance, of insects on frosted beech trees by experimentally inflicting the frost damage. They concluded that the reduced performance was because the experimental conditions differed from that in natural conditions where the performance of the insects is greater.…”
Section: Discussionmentioning
confidence: 99%